The meaning of the dulang dance movement as a traditional dance in traditional ceremonies in Langkat Regency, North Sumatra, Indonesia - Fitri, Aida; Basri, Novysa; Ramdiana , Ramdiana; Aiman, Umul; Saputra , Rudy Juli; Hidayani, Novita; Rahmad , Rizki; Wahyudi , Wahyudi (Pascasarjana Institut Seni Indonesia Surakarta, 2024)
The purpose of this study is to explore the meaning of the Dulang Dance. In this study, the method chosen is a qualitative descriptive method. The data collection process was carried out through observation, conversation, and document recording, aiming to explore the significance of the implied meaning in the Dulang Dance movements. This qualitative research is able to provide insight into the meaning contained in the Dulang Dance in Langkat. The findings of the study revealed that in the sembah movement when greeting the host of the event, each movement has its own symbolic value. Such as the contour of the sembah movement following the direction of the wind, and the low horse stance position that represents stability. In addition, the sitting position is similar to the tahyad prayer, but with the legs more open and not overlapping, expressing deep respect. The gentle movements in the martial art of silat, still contain strength and spirit, while the steps on the plate and the jumps onto the dulang have deep philosophical meanings. All of this symbolizes an expression of gratitude to the Creator, respect for respected individuals, as well as the values ​​of simplicity, humility, and respect for religion. The implication of the greeting to the steps on the stage, Dulang Dance expresses gratitude to Allah SWT while respecting the King or leader. For the future, the young generation can preserve the meaning of Dulang Dance.